1980
DOI: 10.1007/bf00000954
|View full text |Cite
|
Sign up to set email alerts
|

A review of some physiological and toxicological responses of freshwater fish to acid stress

Abstract: SynopsisData relating to the specific effect of low pH on growth of freshwater fishes are ambiguous. Reproductive failure resulting from acid stress appears to be related to an upset in calcium metabolism and to faulty deposition of protein in developing oocytes. It appears that the 'no effect' level of pH depression for successful reproduction is around 6.5. Data on behaviorial responses of freshwater fish to acid stress and CO, are described. Most fish appear to be indifferent to pH within the range of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
1
7

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(93 citation statements)
references
References 51 publications
3
80
1
7
Order By: Relevance
“…However, since mucus is initially synthesized as basic or neutral glycoproteins (Mittal et al 1980), an increased PAS-reactivity could also reflect a predominance of newly differentiated mu cous cells, and an increased turnover of this cell-type (Iger et al 1988;. The presence of a mucus layer attached to the epidermal sur face after fixation of the skin from acid-exposed trout may indicate that its composition has changed, although Fromm (1980) has suggested that this might be caused by coagulation in low pH conditions. The appearance of newly differentiated mucous cells close to the skin sur face in acid treated fish has not previously been reported for rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…However, since mucus is initially synthesized as basic or neutral glycoproteins (Mittal et al 1980), an increased PAS-reactivity could also reflect a predominance of newly differentiated mu cous cells, and an increased turnover of this cell-type (Iger et al 1988;. The presence of a mucus layer attached to the epidermal sur face after fixation of the skin from acid-exposed trout may indicate that its composition has changed, although Fromm (1980) has suggested that this might be caused by coagulation in low pH conditions. The appearance of newly differentiated mucous cells close to the skin sur face in acid treated fish has not previously been reported for rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the acidification, fish populations are vanishing, especially in poorly buffered areas like Scandinavia, Canada and the north-eastern U.S.A. (Beamish, 1976;Leivestad & Muniz, 1976). The main causes for the disappear ance of fish populations are osmoregulatory stress, disturbances of the acid-base balance, increased gill diffusion distance resulting in hypoxia, reduced reproduc tive capacity, changes in predator-prey interactions, impaired growth, and an accumulation of aluminium and heavy metal ions in the acidified waters (Fromm, 1980). The resulting physiological and endocrinological changes observed in fish after exposure to water acidification can be studied systemati cally only in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…It caus es disturbance of water and ion balance, reduced growth and reproduction, and may eventually lead to disappear ance of fish populations (Fromm 1980;M cD onald 1983;Wendelaar Bonga and Dederen 1986). The disturbance of the water and ion balance is mainly caused by dam age inflicted upon the gills, and, as a consequence, many au thors have examined the histopathological effects of acid Correspondence to: S.E.…”
Section: Introductionmentioning
confidence: 99%